If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -2 + 3x = 17 + 12x + -23 Combine like terms: 5 + -2 = 3 3 + 3x = 17 + 12x + -23 Reorder the terms: 3 + 3x = 17 + -23 + 12x Combine like terms: 17 + -23 = -6 3 + 3x = -6 + 12x Solving 3 + 3x = -6 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 3 + 3x + -12x = -6 + 12x + -12x Combine like terms: 3x + -12x = -9x 3 + -9x = -6 + 12x + -12x Combine like terms: 12x + -12x = 0 3 + -9x = -6 + 0 3 + -9x = -6 Add '-3' to each side of the equation. 3 + -3 + -9x = -6 + -3 Combine like terms: 3 + -3 = 0 0 + -9x = -6 + -3 -9x = -6 + -3 Combine like terms: -6 + -3 = -9 -9x = -9 Divide each side by '-9'. x = 1 Simplifying x = 1
| 2(1+2)=1(2+3x) | | 5(6x-8)=10+5x | | 3-5(-7+x)=-32+5x | | 5(6x-8)=10 | | -13=-(-7+b) | | 0.15x+0.05(12-x)=0.10(-10) | | -4(v+5)=-25-5v | | 6(1+6n)+6=5(6n+2)+8n | | 1000*y=2.7963 | | -28+8m=-6(6-2m)-4 | | j^2-8= | | W^2+5w-44=0 | | 4.2*y=39.06 | | -3(1-6m)+6=3(m+1) | | n=3n-f | | 8n+33=-7(n+6) | | 0.5x-2.5=3.9x+2.4 | | (x^3-5x^2+12x+18)(x-2)= | | 28+3p=-1-7(5-5p) | | 28-0.03y=0.07y-12 | | -(r-7)+1=14-3r | | 5x+20=250 | | 5n-4=-19 | | -8(3x+7)=28+4x | | 5+7(7-8a)=390 | | 15=(2t-1) | | f(x)=(x-5)(x+6)(x+2) | | (x^2-6x+18)(x+1)= | | 0.4x+4.9=3.9 | | -2(1-8k)=126 | | 2a-7a=2a | | (5x+6)(4y-5)= |